Effects of HIV voluntary medical male circumcision programs on sexually transmitted infections. Issue 1 (10th February 2021) - Matoga, Mitch; Hosseinipour, Mina C.; Jewett, Sara; Hoffman, Irving F.; Chasela, Charles
Abstract : Purpose of review: Evidence of the protective effect of voluntary medical male circumcision (VMMC) against HIV is well established. However, evidence of the protective effect of VMMC against other sexually transmitted infections (STIs) has been inconsistent or scarce across different populations and settings. This review summarizes the current evidence on the effect of VMMC for HIV prevention on acquisition and transmission of other STIs in heterosexual men, women, and men who have sex with men (MSM). Recent findings: Recent findings continue to strongly support the protective effect of male medical circumcision against acquisition and transmission of herpes simplex virus type 2 (HSV-2), human papillomavirus (HPV) and syphilis infections in heterosexual men and women, and bacterial vaginosis and trichomoniasis in women. There is emerging evidence on the protective effect of VMMC against acquisition of hepatitis B and Mycoplasma genitalium infections in heterosexual men, and HSV-2, HPV, and syphilis in MSM. Summary: Evidence on the protective effect of VMMC against acquisition and transmission of common STIs is available for heterosexual men and women but more evidence is required for MSM. This review supports policy recommendations for the protective benefits of VMMC against STIs.